A Hate and Provocative Speech Act in Social Media: A Forensic Linguistics Study - Sarifuddin Sarifuddin; Maknun Tadjuddin; Ery Iswary (ELS Journal on Interdisciplinary Studies in Humanities, 2021)
This study aims to: (1) explain the types of provocative speech acts of Natalius Pigai on YouTube social media, (2) explain the forms of provocative speech acts on YouTube social media. The data in this study are languages ​​that are supposed to contain provocative criminal acts on YouTube social media. The data source in this study is the social media YouTube. The method used in this research is descriptive qualitative method, data collection techniques in the form of viewing and documentation. The data were analyzed using the steps of (1) identifying, (2) classifying, and (3) analyzing. The results of this study indicate that: Natalis Pigai's utterances on social media contain literal indirect speech acts, while locutionary speech acts use declarative locutions, expressive illocutions, and get hearer to think about perlocutions (make the interlocutor think about). These statements violate the Criminal Code, Article 160 and Article 161 regarding sedition. Keywords: provocative speech acts, social media, forensic linguistics. Keywords: provocative speech, social media, forensic linguistics.